An Empirical Study of Dynamic Capability: Leveraging The Roles of Virtual Leadership and Relational Capital - Asti Khoerunisa; Iwan Hermawan; Rustono Rustono (Research Synergy Foundation, 2024)
The problems that arise are the lack of co-creation product development, low technology utilization, and organizational difficulties in adapting to market changes. From these problems, this study offers the role of dynamic capability (DC) to be adaptive during market changes by optimizing organizational resources in creating creativity. DC requires the role of virtual leadership (VL) and relational capital (RC) to encourage creative performance (CP). The evidence gap is another problem in the form of contradiction in the research results on the influence of VL on CP, which are still inconclusive. This research empirically tests the role of DC with VL and RC as antecedent variables that can be used as strategies for achieving CP. The sampling technique used was purposive sampling to obtain 180 respondents who are creative industry leaders in Central Java. This study uses the perspective of dynamic capability theory (DCT). The analysis tool is structural equation modeling (SEM), which is processed using AMOS software. The results of this study empirically prove that the role of DC can be fully mediated. This study provides practical contributions for managers to encourage organizational members to improve sensing, learning, integration, and reconfiguration capabilities in using virtual technologies and networked organizations.